A Glycosylated Covalent Organic Framework Equipped with BODIPY and CaCO3 for Synergistic Tumor Therapy - Guan, Qun; Zhou, Le‐Le; Lv, Fan‐Hong; Li, Wen‐Yan; Li, Yan‐An; Dong, Yu‐Bin (Angewandte Chemie International Edition, 2020)
Ca2+, a ubiquitous but nuanced modulator of cellular physiology, is meticulously controlled intracellularly. However, intracellular Ca2+ regulation, such as mitochondrial Ca2+ buffering capacity, can be disrupted by 1O2. Thus, the intracellular Ca2+ overload, which is recognized as one of the important cell pro‐death factors, can be logically achieved by the synergism of 1O2 with exogenous Ca2+ delivery. Reported herein is a nanoscale covalent organic framework (NCOF)‐based nanoagent, namely CaCO3@COF‐BODIPY‐2I@GAG (4), which is embedded with CaCO3 nanoparticle (NP) and surface‐decorated with BODIPY‐2I as photosensitizer (PS) and glycosaminoglycan (GAG) targeting agent for CD44 receptors on digestive tract tumor cells. Under illumination, the light‐triggered 1O2 not only kills the tumor cells directly, but also leads to their mitochondrial dysfunction and Ca2+ overload. An enhanced antitumor efficiency is achieved via photodynamic therapy (PDT) and Ca2+ overload synergistic therapy. A multifunctional COF‐based nanoagent, which is equipped with BODIPY‐2I photosensitizer, CaCO3 nanoparticle, and glycosaminoglycan (GAG) targeting agent, can be a highly efficient and selective antitumor nanomedicine for colon tumor via photodynamic therapy (PDT) and Ca2+ overload synergistic therapy.